High-Intensity Interval Training and Its Effects on Cardiorespiratory Fitness and Body Mass Index in Children and Adolescents with Overweight or Obesity: A Narrative Review - Bolek, Oliwia; Grzelak, Oliwia; Kuśmierczyk, Weronika; Sordyl, Katarzyna; Szczepański, Piotr; Rogulski, Krzysztof; Majkowska, Magdalena; Fengier, Maria; Kącikowska, Justyna; Trzaskowski, Jakub (Journal of Education, Health and Sport, 2026)
Background. The global prevalence of overweight and obesity among children and adolescents has increased markedly in recent decades and represents a major public health concern. High-intensity interval training (HIIT) has emerged as a time-efficient exercise strategy that may improve cardiorespiratory fitness (CRF) and cardiometabolic health. However, its effectiveness in youth with overweight or obesity is still not fully understood. Methods. A narrative literature review was conducted to examine the effects of HIIT on CRF and body mass index (BMI) in children and adolescents with overweight or obesity. PubMed, Embase, Google Scholar, and Web of Science were searched for studies published between June 2016 and March 2026. Eligible studies included structured multi-session HIIT interventions lasting at least four weeks in participants aged 6–18 years. Primary outcomes were CRF and BMI. Due to heterogeneity in study design and protocols, findings were synthesized narratively. Results. Nine intervention studies met the inclusion criteria. Most studies (7 of 9) reported improvements in cardiorespiratory fitness, including increases in VO₂max, VO₂peak, maximal aerobic speed, or shuttle-run performance after 8–12 weeks of HIIT. Effects on BMI and body composition were less consistent. Approximately half of the studies observed reductions in BMI or BMI z-score, though not consistently greater than those seen with moderate-intensity continuous training or lifestyle interventions. Some studies also reported improvements in cardiometabolic markers such as blood pressure and metabolic parameters. Conclusion. HIIT appears to be an effective and time-efficient strategy for improving cardiorespiratory fitness in children and adolescents with overweight or obesity. Although its impact on BMI is less consistent, HIIT may still contribute to improved cardiometabolic health and promote physical activity in youth.